PROSPECTS FOR EXPORT DEVELOPMENT OF TRANSPORT AND LOGISTICS SERVICES OF RUSSIA - D. I. Tkachenko (Вестник университета)
Export of transport and logistics services has been analysed and ways of its development based on factors that affect the growth of exports have been proposed. The main problems that hinder the development of both services exports and the transport system as a whole, which are reduced to a lag in the technical and technological level and low competitiveness of domestic companies, have been outlined. The expediency of innovative way of developing the transport system through the formation of transport and logistics clusters, infrastructure development and the introduction of new technologies has been substantiated. Taking into account the large volume of world cargo transport by sea, the development of seaports is of great importance. The need is noted for state support not only for large enterprises, but also for small companies specializing in the development and implementation of innovations in transport services. The issue of increasing the volume of transport services through the development of the Northern sea route and the implementation of the Silk Road Economic Belt project has been considered.